Next Direct Left Maximum Minimum Economical Process -Protected and Unbalanced Lattice in Cloud Figuring - et. al., K. Thiagarajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Objective: Main Objective of this study is to find the minimum cost of the corresponding Payoff. Method: We Proposed “NILMMA” is to find and fix the cost in minimum level for the transportation problem, it reduced the runtime for finding the optimum cost than the existed methods in Operation research field. Also the proposed algorithm is very efficient and easy to understand.